KAJIAN KONTEKSTUALISASI ATAS PEMBAHARUAN HUKUM KELUARGA ISLAM DI NEGARA MUSLIM - Muhammad Mahmud Nasution (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
The issue of family law is still an interesting discussion both in the world of education and in the politics of legislation, this issue is interesting because it has enormous implications in everyday life. So that there is a need for a significant regulation in this matter, the legislature is expected to be able to bring forth a family law reform that is able to become a buffer that is in accordance with the conditions of life in the family at this time.In modern times, the existence of Islamic law is relatively different from the Islamic law contained in classical fiqh books and also with the view of the eternity of Islamic law above. The reform of Islamic law was carried out in Islamic countries in Europe, Africa, Asia, and even in the Middle East, there were major changes that had never happened before in the last century.In this study, we will only discuss a small part of several Muslim countries that have reformed Islamic family law. The countries that will be discussed are Turkey, Egypt, and Indonesia. Turkey and Egypt are considered as pioneers in the renewal of Islamic family law in the world, because it is these two countries that have reformed Islamic family law for the first time.